The importance of the dentistry professionals participation in the coping strategies with the human papillomavirus (HPV) infection - Moreira, Luiz Carlos; Moleri, Andrea Braga; Cruz, Darlynne Fugueira Marques da; Oliveira, Wirys dos Reis (Brazilian Journal of Sexually Transmitted Diseases, 2018)
Epidemiological studies have shown that infection by the Human Papillomavirus (HPV) is characterized as pandemic. Therefore, it constitutes a serious public health problem(1). HPV does not observe cultural, social or economic rules, unlike certain infections that affect the economically disadvantaged countries, challenging the best health systems. The HPV oncogenic activity is responsible for 28% of all types of cancer associated with infections in the world. Studies in Brazil indicate that HPV, as a persistent infection, is responsible for almost all cervical cancers and numerous other malignancies in different organic sites as vulva, vagina, anus, penis and oropharynx. In Brazil, the oropharyngeal carcinomas associated with this virus represent 72%. In the United States, in Australia and in Northern Europe, the percentage corresponds to 50% of all cases(2,3).